DUKUNGAN KELUARGA DAPAT BERPENGARUH PADA KUALITAS HIDUP PASIEN KANKER PARU YANG MENJALANI KEMOTERAPI - Putri, Diyanah Syolihan Rinjani; Utami, Mega; Fitriana, Rufaida Nur; Yulianto, Sigit (Journal of Advanced Nursing and Health Sciences, 2023)
Cancer is a disease caused by abnormal cell growth that turns into cancer cells. Normally, cells will only divide if there is dead or damaged cell needs to be replaced. Patients with lung cancer undergoing chemotherapy cannot be separated from the experience of decreased quality of life, namely physical, psychological, social and environmental discomfort. It is important to pay attention to the four domains so that patients with lung cancer patients undergoing chemotherapy have a better quality of life through family support and the patients will also have hopes and goals in life. The purpose of this study is to determine the relationship between family support and the quality of life of patients with lung cancer undergoing chemotherapy at Regional Public Hospital of DR. Moewardi. The researcher used an observational analytic design with a cross-sectional approach. The population in this study were 61 respondents. Sampling was conducted using total sampling technique with a sample of 61 respondents. Data were collected using questionnaires. The results showed that the family support for lung cancer patients undergoing chemotherapy was high (67.2%), the quality of life for lung cancer patients undergoing chemotherapy was good (88.52%). Analysis of the data using the Spearman rank test with P value = 0.016 with (p <0.05) indicating that family support significantly related with the quality of life of patients with lung cancer undergoing chemotherapy, with r value = 0.308 with moderate correlation strength. The conclusion of the study is that there is a relationship between family support and quality of life of patients with lung cancer undergoing chemotherapy at RSUD DR. Moewardi. This research can be used as information on health and nursing services for the community about lung cancer.